Mahasiswa : teknologi digital, pembelajaran siswa, Pendidikan anak SD - Fikri, Moh Adiel; Andriyan, Moh; Fahmi, Hasan (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
In an increasingly connected world, apps and digital platforms play a crucial role in everyday life. From social media to e-commerce applications, the existence of this technology not only makes communication easier, but also opens up new opportunities in education. In this article, we will discuss the benefits that can be obtained, the challenges that may be faced, and concrete steps that can be taken to increase the effectiveness of using this technology. With the right insights, readers will be able to optimize the potential of digital applications and platforms in everyday life. Cultivating digital applications and platforms means developing, managing and utilizing these various technologies to achieve greater goals. This includes understanding user needs, developing relevant features, as well as effective marketing strategies. The development of digital technology has had a significant impact on various aspects of life, including in the educational, economic and social fields. Digital applications and platforms are now tools that not only support daily activities, but also open up new opportunities for innovation and productivity. This article aims to examine the importance of cultivating and utilizing digital applications and platforms in modern life. By utilizing existing applications and platforms, people can optimize resources, speed up access to information, and increase efficiency in various sectors. This research also highlights the challenges faced in the process of adapting to digital technology, such as the digital divide and data security, and provides solutions to overcome these obstacles